EFFECT OF PARAMETER CONDITION ON SURFACE ROUGHNESS FOR MACHINING AISI D2 HARDENED TOOL STEEL - Izamshah, R.; Mo, J.P.T.; Arfauz, M.; Ding, S.; Azam, M.A.; Kasim, M.S. (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Hardened steel such as AISI D2 is often used in mould and die industry. Some of the application required to have good surface quality profile and sophisticated free-form shape simultaneously. In current industry practice, manual polishing and grinding is often performed to achieve the required machining tolerance which tends to lower the productivity and difficulty in ensuring the component accuracy. Machining surface roughness is directly affected by the milling parameter and should be methodically analyzed. Thus, this paper aims to study the effect of milling parameter on surface roughness of AISI D2 tool steel. Response Surface Methodology (RSM) technique was used to evaluate the influence of milling parameter namely cutting speed, feed rate and depth of cut on machined surface. From the conducted study, based on the statistical analysis result it is found that feed rate is the main factor that influence the surface roughness followed by milling speed and depth of cut. In addition, the machined surface roughness observed was between 1.5 to 4.5 μm Ra.